2019
DOI: 10.1111/1471-0528.15579
|View full text |Cite
|
Sign up to set email alerts
|

Significance of progesterone receptors (PR‐A and PR‐B) expression as predictors for relapse after successful therapy of endometrial hyperplasia: a retrospective cohort study

Abstract: Objective After successful progestin therapy for endometrial hyperplasia (EH), the risk of relapse remains. We aimed to assess if immunohistochemical (IHC) expression of progesterone receptor isoforms, PR‐A and PR‐B, in endometrial glands and stroma in pre‐treatment endometrial biopsies was related to relapse of EH. Design and setting Biopsy material originated from women with low‐risk and medium‐risk EH recruited to a recent Norwegian multicentre randomised trial. Participants (n = 153) had been treated for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
0
21
0
5
Order By: Relevance
“…Many studies investigating BMI reported that obesity was associated with failure to achieve disease regression and increased recurrence (105,(127)(128)(129)(130) . However, a recent study of Japanese women reported that lower BMI was associated with increased recurrence (131) , whilst numerous studies have reported no association between BMI and outcome (132)(133)(134)(135)(136)(137) . The association between age or menopause status and outcome are also conflicting, with two studies reporting younger age or premenopausal status were associated with disease regression or reduced recurrence (127,132) , whilst another reported younger age was associated with increased recurrence (136) .…”
Section: Systematic Review Of Biomarkers Of Progestin Responsementioning
confidence: 99%
“…Many studies investigating BMI reported that obesity was associated with failure to achieve disease regression and increased recurrence (105,(127)(128)(129)(130) . However, a recent study of Japanese women reported that lower BMI was associated with increased recurrence (131) , whilst numerous studies have reported no association between BMI and outcome (132)(133)(134)(135)(136)(137) . The association between age or menopause status and outcome are also conflicting, with two studies reporting younger age or premenopausal status were associated with disease regression or reduced recurrence (127,132) , whilst another reported younger age was associated with increased recurrence (136) .…”
Section: Systematic Review Of Biomarkers Of Progestin Responsementioning
confidence: 99%
“…Here, a normal endometrium is composed of stromal cells which express an abundant amount of the PR and results in a paracrine effect in epithelium proliferation and differentiation. 90 , 91 Even though stroma decidualization is the main result of the actions of progesterone, the most pronounced difference between PR expression in infertile females and fertile controls occurs in epithelial cells. 92 …”
Section: Resultsmentioning
confidence: 99%
“…Here, a normal endometrium is composed of stromal cells which express an abundant amount of the PR and results in a paracrine effect in epithelium proliferation and differentiation. 90,91 Even though stroma decidualization is the main result of the actions of progesterone, the most pronounced difference between PR expression in infertile females and fertile controls occurs in epithelial cells. 92 While most studies suggest a characteristic change in the receptor expression of steroid hormones in the eutopic endometrium (endometriosis), a study from the Sao-Paulo University (Brazil) showed no significant differences in PR expression compared to the control group.…”
Section: Dovepressmentioning
confidence: 99%
“…It is easy to differentiate between PR-A and PR-B using western blotting because their molecular weights markedly differ. Immunohistochemistry (IHC) can also be used to identify them in clinical biopsy specimens ( 151 ), but antibodies used for the detection of PR-A have been found to detect not only PR-A but also PR-B ( 152 ). Thus, developing new antibodies to distinguish one isoform from the other is pivotal for predicting tumor malignancy and for the clinical prognosis of patients.…”
Section: Regulatory Network Of the Progesterone Axis In Cscsmentioning
confidence: 99%